Firm Cost Level and Shareholder Wealth Among Listed Healthcare Firms in Nigeria - Onyeogubalu Ogochukwu Nkiru; Akwuobi Bridget Udekwesili (International Journal of Financial, Accounting, and Management, 2026)
Purpose: This study examines the effect of firm cost levels on shareholder wealth among listed healthcare firms in Nigeria from 2015 to 2024. This study is unique because it explores how major cost components influence shareholder wealth in the health sector, whereas prior studies in Nigeria have focused mainly on profitability in manufacturing and consumer goods firms. Research Methodology: An ex-post facto research design was employed to examine seven healthcare companies listed on the Nigerian Exchange Group. Four firms were selected using purposive sampling, specifically those with complete financial records. Secondary data for the 10-years were extracted from firms published annual reports and audited financial statements. Panel Least Squares (PLS) regression was used to test the hypotheses. Results: The cost of sales has a positive but non-significant effect on shareholder wealth (? = 0.7894, p = 0.1325), and administrative costs have a positive and significant effect on shareholder wealth (? = 2.9654, p = 0.0044). Conclusions: Cost elements in healthcare operations are not merely burdens on profitability but serve as necessary investments in service delivery, quality assurance, and operational efficiency, which ultimately enhance shareholder value. Limitations: The study's small sample size (four firms) and focus on listed healthcare firms in Nigeria may limit its generalizability to other sectors. Contributions: Healthcare management and finance disciplines Reveals the positive impact of strategic cost management (administrative costs) on shareholder wealth in healthcare firms. Healthcare firms (management, investors) and policymakers in Nigeria: Supports policymakers in understanding the cost dynamics in healthcare.